Singing Techniques and Styles of Specific Sangzhi Folk Song Works - Xuming , Li; Ut-sa, Zurazak; Sopolpong, Thayarat (Journal of Roi Kaensarn Academi, 2024)
This article examines the singing techniques and performance styles of Sangzhi folk songs, a vital element of China’s intangible cultural heritage, highlighting their evolution from traditional to modern forms. Traditional Sangzhi folk songs, such as "Plant a Few Rows of Celery and Chives," emphasize natural, expressive vocal techniques, free rhythmic structures, and ornamentation deeply rooted in the Tujia and Bai dialects. These elements preserve linguistic and cultural authenticity while reflecting the historical and rural contexts of their origins. In contrast, modern Sangzhi folk songs, exemplified by "Hang a Lamp at the Door," integrate Mandarin, contemporary instrumentation, and refined vocal techniques to appeal to broader audiences and address modern themes. The study underscores the dynamic interplay between preservation and innovation, as traditional styles prioritize improvisation and raw emotional delivery, while modern adaptations incorporate structural precision and thematic expansion. Together, these approaches ensure the continued relevance and vitality of Sangzhi folk songs, enriching their status as a living art form and a testament to cultural resilience.